Kiai Sebagai Figur Toleransi Kearifan Lokal di Lasem - Izzati, Afina (FIKRAH, 2020)
This article wants to portray the role of Kyai as inspiration for tolerance in Lasem Central Java, Indonesia. Inter-religious tolerance as Lasem peoples' local wisdom. This research focuses on a complete picture of the phenomenon being studied. The approach used is a case study by exploring community interactions in the research object. In-depth interviews were done to get the data. The result of this research shows that tolerance is an appreciation and respect between individuals or groups with different backgrounds. The role of a kyai to raise people's tolerance, exemplify attitudes, and words to become a role model for the peoples of Lasem. An unwritten rule in the form of tolerance which has become a reference for the community in life and has become local wisdom in Lasem.